2021
DOI: 10.25046/aj060337
|View full text |Cite
|
Sign up to set email alerts
|

Optical Satellite Images Services for Precision Agricultural use: A Review

Abstract: The recent advances in geoscience technologies and earth observation tools have evolved in recent years in a fast cadence. Since 1980 with the apparition of Landsat mission firstly named the Earth Resources Technology Satellite, with 80 m spatial resolution; the ability to capture finest details was limited. The emergence of new concepts in agriculture like digital agriculture and precision agriculture (PA) was challenging the capacity of satellite images to capture the variation within the field. The domain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…This technology plays a pivotal role in precision agriculture, providing farmers with a comprehensive and macroscopic view of their fields. These high-resolution images captured from space offer detailed insights into crop health, soil conditions, and overall field variability [34]- [36]. With the ability to cover vast agricultural landscapes, satellite imagery enables farmers to monitor large areas efficiently, identifying patterns, anomalies, and potential issues.…”
Section: Satellite Imagerymentioning
confidence: 99%
“…This technology plays a pivotal role in precision agriculture, providing farmers with a comprehensive and macroscopic view of their fields. These high-resolution images captured from space offer detailed insights into crop health, soil conditions, and overall field variability [34]- [36]. With the ability to cover vast agricultural landscapes, satellite imagery enables farmers to monitor large areas efficiently, identifying patterns, anomalies, and potential issues.…”
Section: Satellite Imagerymentioning
confidence: 99%
“…According to Dakir et al (2021), some recent studies have shown the possibility of using Earth Observation Satellites (EOS) to manage the agricultural sector. The applications make it possible to detect agricultural diseases, which is likely to establish a suitable way of intervention and an adequate amount of pesticide to apply (Miranda et al 2020;Sambasivam and Opiyo, 2020).…”
Section: Satellites In the Management Of Water Resources In Agriculturementioning
confidence: 99%